UPAYA GURU DALAM MEMBENTUK KARAKTER RELIGIUS ANAK USIA DINI DI TK ISLAMIYAH PONTIANAK TENGGARA (Efforts of teachers in forming the religious character of early childhood in Southeast Pontianak Islamic Kindergarten) - Hazliza Hazliza; Aunurrahman Aunurrahman; Annisa Amalia (Universitas Tanjungpura, 2022)
This study aims to describe the efforts of teachers in shaping the religious character of early childhood in TK Islamiyah Pontianak Tenggara. The research method used is a descriptive method with a qualitative research form. The subjects in this study were seven teachers who taught at the TK Islamiyah Pontianak Tenggara. Data collection techniques used are observation, interviews, and documentation. The results of the research show that: 1. The teacher provides knowledge (moral knowing) in a way that is easy for children to understand, such as through advice, stories, moral messages, songs, and clapping 2. The teacher instills a love for children (moral feeling) by making religious habituation programs such as reading daily prayers, practicing prayers, TPA (al-Quran educational park), and giving rewards in the form of praise are carried out so that children can understand, feel, and can get used to doing worship activities with pleasure, 3. The teacher provides examples and role models (moral action) by leading children in praying before and after activities, guiding children to carry out worship activities such as praying with the right movements, thus the teacher's efforts to shape the religious character of early childhood in TK Islamiyah Pontianak Tenggara have been carried out properly.